The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/21655979.2021.1946632
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a five-lncRNA signature for predicting survival with targeted drug candidates in ovarian cancer

Abstract: The dysregulation of long non-coding RNAs (lncRNAs) plays a crucial role in ovarian cancer (OC). In this study, we screened out five differentially expressed lncRNAs (AC092718.4, AC138035.1, BMPR1B-DT, RNF157-AS1, and TPT1-AS1) between OC and normal ovarian based on TCGA and GTEx RNA-seq databases by using Kaplan-Meier analysis and univariate Cox, LASSO, and multivariate Cox regression. Then, a risk signature was constructed, with 1, 3, 5-year survival prediction accuracy confirmed by ROC curves, and an online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Wang et al found that NRAV can mediate the activation of the Wnt/bcatenin signaling pathway to promote the proliferation and invasion of hepatocellular carcinoma (41). Lin et al discovered that BMPR1B-DT is a prognostic marker of ovarian cancer and is associated with drug sensitivity (42). The role of OLMALINC in osteosarcoma was confirmed by He et al, who found that it was highly correlated with the immune microenvironment of osteosarcoma and could assess patient outcomes (43).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Wang et al found that NRAV can mediate the activation of the Wnt/bcatenin signaling pathway to promote the proliferation and invasion of hepatocellular carcinoma (41). Lin et al discovered that BMPR1B-DT is a prognostic marker of ovarian cancer and is associated with drug sensitivity (42). The role of OLMALINC in osteosarcoma was confirmed by He et al, who found that it was highly correlated with the immune microenvironment of osteosarcoma and could assess patient outcomes (43).…”
Section: Discussionmentioning
confidence: 97%
“…Lin et al. discovered that BMPR1B-DT is a prognostic marker of ovarian cancer and is associated with drug sensitivity ( 42 ). The role of OLMALINC in osteosarcoma was confirmed by He et al., who found that it was highly correlated with the immune microenvironment of osteosarcoma and could assess patient outcomes ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that only about 1.5% of the human genome encodes proteins, and most of the genome is transcribed, non-coding RNAs such as lncRNAs may play crucial roles in biological processes ( 7 ). Researchers have increasingly found that lncRNAs play an important role in tumor biology ( 5 , 32 ). Herein, we investigated the role of LINC00467 in LUAD and demonstrated that DNA copy amplification and hypomethylation were two vital mechanisms of LINC00467 upregulation and were associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…12 necroptosis-related lncRNAs highly associated with OS in glioma patients were identified by lasso and univariate and multifactorial Cox regression, and risk prognostic models were constructed by risk score (i.e., AC025857.2, AC092718.4, AL513534.1, AC083864.2, ZNF236-DT, AC099850.3, AL590094.1, AC010226.1, POLR2J4, AC023024.1, SLC25A21-AS1, and AC109439.2). In these lncRNAs, AC092718.4 has been reported to be highly correlated with ovarian cancer as a predictive signature [22]. AC099850.3 has been found to promote proliferation and invasion in hepatocellular carcinoma via the PRR11/PI3K/AKT pathway and is also a major participant in prognostic models for squamous cell carcinoma of the tongue and non-small-cell lung cancer [23][24][25].…”
Section: Discussionmentioning
confidence: 99%